Differential hippocampal and retrosplenial involvement in egocentric-updating, rotation, and allocentric processing during online spatial encoding: an fMRI study - Gomez, Alice; Cerles, Mélanie; Rousset, Stéphane; Rémy, Chantal; Baciu, Monica (Frontiers in Human Neuroscience, 2014)
The way new spatial information is encoded seems to be crucial in disentangling the role of decisive regions within the spatial memory network (i.e., hippocampus, parahippocampal, parietal, retrosplenial...). Several data sources converge to suggest that the hippocampus is not always involved or indeed necessary for allocentric processing. Hippocampal involvement in spatial coding could reflect the integration of new information generated by ‘online’ self-related changes. In this fMRI study, the participants started by encoding several object locations in a virtual reality environment and then performed a pointing task. Allocentric encoding was maximized by using a survey perspective and an object-to-object pointing task. Two egocentric encoding conditions were used, involving self-related changes processed under a first-person perspective and implicating a self-to-object pointing task. The Egocentric-updating condition involved navigation whereas the Egocentric with rotation only condition involved orientation changes only. Conjunction analysis of spatial encoding conditions revealed a wide activation of the occipito-parieto-frontal network and several medio-temporal structures. Interestingly, only the cuneal areas were significantly more recruited by the allocentric encoding in comparison to other spatial conditions. Moreover, the enhancement of hippocampal activation was found during Egocentric-updating encoding whereas the retrosplenial activation was observed during the Egocentric with rotation only condition. Hence, in some circumstances, hippocampal and retrosplenial structures - known for being involved in allocentric environmental coding - demonstrate preferential involvement in the egocentric coding of space. These results indicate that the raw differentiation between allocentric versus egocentric representation seems to no longer be sufficient in understanding the complexity of the mechanisms involved during spatial encoding.